RDML-Ninja and RDMLdb for standardized exchange of qPCR data - Ruijter, Jan M.; Lefever, Steve; Anckaert, Jasper; Hellemans, Jan; Pfaffl, Michael W.; Benes, Vladimir; Bustin, Stephen A.; Vandesompele, Jo; Untergasser, Andreas (BMC bioinformatics, 2015)
The universal qPCR data exchange file format RDML is today well accepted by the scientific community, part of the MIQE guidelines and implemented in many qPCR instruments. With the increased use of RDML new challenges emerge. The flexibility of the RDML format resulted in some implementations that did not meet the expectations of the consortium in the level of support or the use of elements.